Over a million students use our free study notes to help them with their homework
This problem can be solved through substitution. The first equation provided in the question should be rearranged to give y=2x-2. This equation for y can be directly substituted into the second equation. ...
3^(3/2) = a * 3^(1/2)3^(1/2) * 3^(-2) = 3^(3/2)Therefore a must be equal to 3^(-2)a = 1/9
When solving a simultaneous equation, we will use the elimination method. This method sees us removing or ‘eliminating’ the x or y term. First we need to find the lowest common multiple of the x and y ter...
f'(x) = (3/8)x^2 - 10x^(-1/2) + 1Each term must be integrated (increase the power by 1 and divide by the new power), remembering to include + c.f(x) = (3/8)(x/3)^3 - 10*(2x)^(1/2) + x + cf(x) = (...
First we need to rearrange our equation so it is in the correct form of ax2+bx+c=0.So we'd move the 3 over to the left hand side to give us 2x2-2x-3=0.We need to use the quadratic formula. Usin...
←
498
499
500
501
502
→
Internet Safety
Payment Security
Cyber
Essentials